When Weather Forecasters Are Wrong: Image Repair and Public Rhetoric After Severe Weather. Issue 6 (December 2018) - Compton, Josh
Weather forecasts are a unique type of prediction rhetoric—science communication with inherent uncertainty and multiple potential interpretations from diverse audiences. When forecasts are wrong, audiences often turn their ire toward the weather forecaster. This rhetorical analysis considers image repair efforts of a meteorologist following a botched winter storm forecast. Implications for communication efforts of weather forecasters are offered, in addition to consideration of insight into the larger realm of the rhetoric of science.